Chinese Herbal Medicine Combined With EGFR-TKI in EGFR Mutation-Positive Advanced Pulmonary Adenocarcinoma (CATLA): A Multicenter, Randomized, Double-Blind, Placebo-Controlled Trial - Jiao, Lijing (Front Pharmacol, 2019)
Background: To determine the clinical activity and safety of Chinese herbal medicine (CHM) combined with epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKI) in patients with advanced pulmonary adenocarcinoma (ADC) and the ability of CHM combined with EGFR-TKI to activate EGFR mutations. Methods: Three hundred and fifty-four patients were randomly assigned to EGFR-TKI (erlotinib 150 mg/d, gefitinib 250 mg/d, or icotinib 125 mg tid/d) plus CHM (TKI+CHM, N = 185) or EGFR-TKI plus placebo (TKI+placebo, N = 169). Progression-free survival (PFS) was the primary end point; the secondary end points were overall survival (OS), objective response rate (ORR), disease control rate (DCR), quality of life [Functional Assessment of Cancer Therapy-Lung (FACT-L) and Lung Cancer Symptom Scale (LCSS)], and safety. Results: The median PFS was significantly longer for the TKI+CHM group (13.50 months; 95% CI, 11.20–16.46 months) than with the EGFR-TKI group (10.94 months; 95% CI, 8.97–12.45 months; hazard ratio, 0.68; 95% CI, 0.51–0.90; P = 0.0064). The subgroup analyses favored TKI+CHM as a first-line treatment (15.97 vs. 10.97 months, P = 0.0447) rather than as a second-line treatment (11.43 vs. 9.23 months, P = 0.0530). Patients with exon 19 deletion had a significantly longer PFS than with 21 L858R. The addition of CHM to TKI significantly improved the ORR (64.32% vs. 52.66%, P = 0.026) and QoL. Drug-related grade 1–2 adverse events were less common with TKI+CHM. Conclusions: TKI+CHM improved PFS when compared with TKI alone in patients with EGFR mutation-positive advanced non-small-cell lung cancer (NSCLC). Clinical Trial Registration: www.ClinicalTrials.gov, identifier NCT01745302.